Validity of static fluid practicum guide based on science process skills using kvisoft flipbook maker - Dinda Desma Romadona; Sri Purwaningsih; Darmaji Darmaji (Universitas Negeri Yogyakarta, 2021)
This study aims to develop a physics practicum guide based on science process skills on static fluid material using Kvisoft Flipbook Maker that meets valid criteria or is suitable for use. This study is development research in accordance with the ADDIE model, i.e.: Analysis, Design, Development, Implementation, and Evaluation. The science process skills indicator contained in the practicum guide is an indicator of basic and integrated science process skills by Rezba (2007). The practicum guide is validated by material and media experts and produces excellent assessment results so that it is suitable for use in the physics learning process of senior high school, especially on static fluid topic.